Donor’s Perception Regarding Plasma Donation in Pakistan - Javed, Tauram (South Asian Journal of Social Sciences and Humanities, 2020)
Covid19 is rightly ranked as first international pandemic that within a short span of time covered the globe.  There was no specific medicine to fight Covid-19 in early days (Rubin et al., 2020). But soon it was  discovered that plasma of recovered covid-19 patient could be a hope for the newly affected patient. Fortunately, in Pakistan trails of convalescent plasma therapy proved much better results. But most of  recovered people have fears and myths about plasma donation. This study aimed to motivate the recovered  covid-19 patients to donate plasma generously through removal of apprehensions. plasma. In this cross sectional study, self-generated questionnaire having answer (Yes/No) were designed and got it filled by  112 covid-19 recovered patients on Google forms and tried to find out the views about plasma therapy.  Data is analyzed through SPSS version 26. About 55.5% people think that plasma donation is equal to  blood donation, 50.9% think that plasma donation causes adverse effects on their health after donation.  Amongst the participants in the sample, 73.2% had never donated blood even for a single time in their  lives. The study enabled to know more precisely that why recovered patients avoid to help others to whom  they were a ray of hope. The major deadly concern which kept the healed patient to abstain from plasma  donation was further deterioration of health. While addressing the specific hinderance creating  misconceptions the majority of recovered patients were ready to donate. A strong need is felt to encourage  the mobs to donate blood in general and covid-19 recovered patient should donate their plasma for saving  lives through proper awareness sessions by using social media, print media as well as electronic media.
Keywords: Perception; Blood Donation; Plasma Donation; covid-19; donor; therapy; motivation.